2018
DOI: 10.1017/jfm.2018.305
|View full text |Cite
|
Sign up to set email alerts
|

Swimming performance, resonance and shape evolution in heaving flexible panels

Abstract: Many animals that swim or fly use their body to accelerate the fluid around them, transferring momentum from their flexible bodies and appendages to the surrounding fluid. The kinematics that emerge from this transfer result from the coupling between the fluid and the active and passive material properties of the flexible body or appendages. To elucidate the fundamental features of the elastohydrodynamics of flexible appendages, recent physical experiments have quantified the propulsive performance of flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 76 publications
1
34
0
Order By: Relevance
“…Fluid viscosity affects the forced resonance frequency, although for low fluid damping the resonance frequency overlays with the natural (undamped) frequency. Note that Quinn et al (2014) and Hoover et al (2018) have shown for elastic plates that the maxima of the thrust and tip deflection occur for the same effective flexibility. Thus, the values of D * corresponding to the maximum thrust match the forced resonance frequency.…”
Section: Problem Set-upmentioning
confidence: 92%
See 3 more Smart Citations
“…Fluid viscosity affects the forced resonance frequency, although for low fluid damping the resonance frequency overlays with the natural (undamped) frequency. Note that Quinn et al (2014) and Hoover et al (2018) have shown for elastic plates that the maxima of the thrust and tip deflection occur for the same effective flexibility. Thus, the values of D * corresponding to the maximum thrust match the forced resonance frequency.…”
Section: Problem Set-upmentioning
confidence: 92%
“…(2014) and Hoover et al. (2018) have shown for elastic plates that the maxima of the thrust and tip deflection occur for the same effective flexibility. Thus, the values of corresponding to the maximum thrust match the forced resonance frequency.…”
Section: Problem Set-upmentioning
confidence: 93%
See 2 more Smart Citations
“…Quinn, Lauder & Smits (2014 experimentally investigated the combined impact of St and resonance to improve the propulsive Effect of trailing-edge shape on self-propulsive performance 887 A7-3 performance of a flapping plate. Besides, theoretical works (Alben 2008;Michelin & Llewellyn Smith 2009;Paraz, Schouveiler & Eloy 2016), experiments (Heathcote & Gursul 2007;Heathcote, Wang & Gursul 2008) and numerical simulations (Michelin & Llewellyn Smith 2009;Eldredge, Toomey & Medina 2010;Ferreira de Sousa & Allen 2011;Kang et al 2011;Zhu, He & Zhang 2014;Hoover et al 2018) have been performed to investigate the effect of flexibility on the dynamic performance of plates. In addition, the effect of trailing-edge shape on the self-propulsive speed of flapping flexible plates was investigated experimentally by Lauder et al (2011).…”
Section: Introductionmentioning
confidence: 99%